HUBUNGAN ANTARA EFIKASI DIRI DENGAN INTENSI BERWIRAUSAHA PADA SISWA KELAS XII SMK NEGERI 6 PALEMBANG - Yuliansyah, Yuliansyah; Jahin, Novia Pahleni (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2018)
The purpose of this study was to determine whether there is a relationship between self-efficacy and intention entrepreneurship in class XII Vocational School District 6 Palembang. The study hypothesis is that there is a positive correlation between self-efficacy and intention entrepreneurship to high school students Kejururan Negeri 6 Palembang. The population in this study were students Vocational School District 6 Palembang totaling 357 students, with the number of samples taken are 100 students who are determined using proportional random sampling technique. Data collection instruments used in this study is the scale of self-efficacy and intention scale entrepreneurship. Methods of data analysis using the Pearson product moment correlation. Based on this analysis, showed there was a significant positive relationship between self-efficacy and intention entrepreneurship to high school students SMK Negeri 6 Palembang with r count> r table = 0.370> 0.197 by 0.05. That is, the higher self-efficacy, the higher the intention entrepreneurship.